Modeling of Infantry Attacks on Real Terrain - Pincevičius, A.; Baušys, R.; Bekešienė, S.; Kleiza, V. (Nonlinear Analysis: Modelling and Control, 2008)
The estimation of the terrain features can be completely carried out by using the Geographical Information System (GIS). GIS technologies and three-dimensional map in planning battle tactics are discussed. An infantry attack on real terrain is modeled. The stochastic model of combat is given in article.
Keywords: modeling; military operations; stochastic models; Geographical Information System